Can Radiofrequency Ablation Replace Liver Resection for Solitary Colorectal Liver Metastasis? A Systemic Review and Meta-Analysis - Hao, Wu; Binbin, Jiang; Wei, Yang; Kun, Yan (Frontiers in Oncology, 2020)
Radiofrequency ablation (RFA) can be the favorable option for patients with colorectal liver metastasis (CRLM). However, current reports about therapeutic efficacy of liver resection (LR) and RFA for colorectal liver metastasis (CRLM) still remains controversial, especially solitary CRLM. Therefore, this meta-analysis was performed to evaluate the therapeutic efficacy for solitary CRLM between LR and RFA. Firstly, a comprehensive search for published studies was conducted using PubMed, Cochrane library, and web of science. Each study was reviewed and data extracted. In this meta-analysis, 10 studies (11 study arms) were finally included. The meta-analysis was performed using risk ratio (RR) and random effect model or fixed effect model, in which 95% confidence intervals (95% CI) for RR were calculated. Primary outcomes were the disease-free survival (DFS) and overall survival (OS) and at 1, 3 or 5 years plus complications rate. The results showed that patients treated by LR achieved better PFS and OS than those by RFA, but subgroup analysis and meta-regression displayed that the efficacy of RFA was equivalent to that of LR in solitary CRLM, when conditions limited to tumor≤3 cm, fewer synchronous metastasis in publication year (2011-2018). Meanwhile, RFA achieved lower complication rates when compared with LR. In conclusion, althrough patients treated by RFA cannot achieve better PFS and OS than those by LR, RFA can be considered the noninferior treatment candidate for solitary CRLM, with lower complication rates.